Methods of apoptosis detection - Pedrycz, Agnieszka; Siermontowski, Piotr; Orłowski, Marcin (Current Problems of Psychiatry, 2012)
The aim of present study was analyze of methods of apoptosis detection. We described methods detecting single apoptotic cells and their populations. In those methods we showed: single cell gel electrophoresis (SCGE), apoptotic cell identification using transmission electron microscopy (TEM) and light microscopy; method based on assessment of changes in the apoptotic cell membrane; method based on Caspase 3 activity examination. The other methods exanimate releasing of cytochrome C from the mitochondria and detecting of DNA fragmentation. We described as well flow cytometry (flow cytophotometry). The manuscript was the most focused on immunohistochemical method.